2016
DOI: 10.1007/s00253-016-7596-3
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Pseudomonas aeruginosa and Staphylococcus aureus during co-cultivations and polymicrobial infections

Abstract: Pseudomonas aeruginosa and Staphylococcus aureus are versatile bacterial pathogens and common etiological agents in polymicrobial infections. Microbial communities containing both of these pathogens are shaped by interactions ranging from parasitic to mutualistic, with the net impact of these interactions in many cases resulting in enhanced virulence. Polymicrobial communities of these organisms are further defined by multiple aspects of the host environment, with important implications for disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 75 publications
(100 reference statements)
2
80
0
2
Order By: Relevance
“…[1] The opportunistic human pathogens Pseudomonas aeruginosa and Staphylococcus aureus are both capable of causing ab road variety of diseases,ranging from simple skin infections to lifethreatening sepsis and endocarditis.B oth species are frequently involved in polymicrobial infections where they engage in ab road range of interactions with major impact on the development and progression of infectious diseases. [2] Most frequently,h owever, the interactions of P. aeruginosa and S. aureus have been described as being of competitive nature. [3] Cystic fibrosis patients are initially colonized prevalently by S. aureus,w hich in later stages is largely replaced by P. aeruginosa although neither species completely disappears during any stage of the chronic disease.…”
mentioning
confidence: 99%
“…[1] The opportunistic human pathogens Pseudomonas aeruginosa and Staphylococcus aureus are both capable of causing ab road variety of diseases,ranging from simple skin infections to lifethreatening sepsis and endocarditis.B oth species are frequently involved in polymicrobial infections where they engage in ab road range of interactions with major impact on the development and progression of infectious diseases. [2] Most frequently,h owever, the interactions of P. aeruginosa and S. aureus have been described as being of competitive nature. [3] Cystic fibrosis patients are initially colonized prevalently by S. aureus,w hich in later stages is largely replaced by P. aeruginosa although neither species completely disappears during any stage of the chronic disease.…”
mentioning
confidence: 99%
“…P. aeruginosa and S. aureus coexist within the CF lung, where a heterogeneous array of microorganisms, the host immune system, and nutrient availability all contribute to a complex and dynamic environment (8, 13, 31). Here we demonstrate that alginate, which is known to impact both host-pathogen and pathogen-pathogen interactions, also indirectly impacts pathogen-pathogen interactions (51, 52).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of P. aeruginosa - S. aureus interactions have demonstrated that P. aeruginosa kills S. aureus in vitro , and this interaction is thought to contribute to the dominance of P. aeruginosa over S. aureus as CF patients age (30, 31). Considerable progress has been made in elucidating the mechanism of S. aureus killing mediated by P. aeruginosa (3235).…”
Section: Introductionmentioning
confidence: 99%
“…Die für den Menschen fakultativ pathogenen Bakterien Pseudomonas aeruginosa und Staphylococcus aureus sind beide in der Lage, eine Vielzahl an Krankheiten zu verursachen, die von einfachen Hautinfektionen bis hin zu lebensbedrohlicher Sepsis oder Endokarditis reichen. Beide Spezies sind häufig an polymikrobiellen Infektionen beteiligt, wobei sie durch ihre gegenseitigen Wechselwirkungen einen entscheidenden Einfluss auf die Entwicklung und den Verlauf von infektiösen Krankheiten nehmen . Am häufigsten wurden die Wechselwirkungen zwischen P. aeruginosa und S. aureus allerdings als kompetitiv beschrieben .…”
Section: Figureunclassified